Combination of Youhua Kuijie Prescription and sulfasalazine can alleviate experimental colitis via IL-6/JAK2/STAT3 pathway - Tang, Lili; Liu, Yuedong; Tao, Hongwu; Feng, Wenzhe; Ren, Cong; Shu, Yuping; Luo, Ruijuan; Wang, Xiangyi (Frontiers in Pharmacology, 2024)
Introduction Youhua Kuijie prescription (YHKJ) is a hospital preparation that is composed of nine kinds of herbs. Sulfasalazine (SASP) is widely used as a first-line clinical treatment for UC. Traditional Chinese medicine and Western medicine have their own advantages in the treatment of UC, and the mechanism of YHKJ combined with SASP in the treatment of UC needs to be investigated. Methods In this study, the therapeutic mechanism of YHKJ combined with SASP in the treatment of UC was predicted by network pharmacology and molecular docking. The chemical components and related targets of YHKJ were obtained from the TCMSP database. The chemical structure of SASP was obtained from the PubChem server, and related targets of SASP molecules were identified using the PharmMapper database. UC-related targets were obtained from the DisGeNET, GeneCards, OMIM, TTD, DrugBank and PharmGkb databases. Results In total, 197 shared targets were identified by constructing a Venn diagram. PPI network data obtained from the STRING database were imported into Cytoscape to visualize the “drug-disease” target network, and STAT3 was selected as the core target by topological analysis. Gene Ontology revealed the biological functions of target genes, and KEGG analysis revealed that the core target STAT3 was differentially expressed in Th17 cells and the JAK-STAT signaling pathway. Thus, the core target STAT3 was subjected to molecular docking with the top 10 components, including nine YHKJ components (quercetin, luteolin, ursolic acid, daidzein, kaempferol, wogonin, myricetin, formononetin, indirubin) and SASP (C18H14N4O5S). The molecular docking results showed that STAT3 had favorable binding with the nine YHKJ components and SASP; STAT3 had the strongest binding with ursolic acid (−10.26 kcal/mol), followed by SASP (−8.54 kcal/mol). Qualitative analysis of the chemical constituents of YHKJ by HPLC revealed that sitosterol, ursolic acid, myricetin, daidzein, quercetin, kaempferol and formononetin were the main components. Additional experiments verified that YHKJ combined with SASP inhibited activation of the IL-6/JAK2/STAT3 pathway and alleviated inflammation in UC model rats. Discussion Our results showed that seven chemical components in YHKJ cooperate with SASP to interfere with activation of the IL-6/JAK2/STAT3 pathway, thus playing a role in the treatment of UC.